Factors that influence employee’s job performance in Majlis Bandaraya Petaling Jaya (MBPJ) / Jami Jahirah Jamiluddin - Jamiluddin, Jami Jahirah (Faculty of Business and Management, 2020)
This research is conducted to determine the factors that influence employee’s job performance in Majlis Bandaraya Petaling Jaya. The study was conducted by distributing 120 sets of questionnaires, which all of it were being distributed conveniently for the employee in Majlis Bandaraya Petaling Jaya (MBPJ) tower. All the questionnaires were answered by respondent using a printed questionnaire. The distribution of questionnaire by hand were done from 4th until 8th November 2019 and the time of distribution are starting from 9 am until 4.30 pm. The information gathered were assessed using the Social Science Statistical Package (SPSS) version 22. Based on the data finding, it shows that three out of four independent variable which is leadership, training and development, benefits and rewards have significant relationship towards job performance. However, there is no significant relationship between work environment and employee’s job performance in Majlis Bandaraya Petaling Jaya.